Over a million students use our free study notes to help them with their homework
When I am expanding brackets I use the acronym FOIL and simplify. You begin by multiply the first term (F) in each bracket, followed by multiplying the outside terms (O), then the inside terms (I) and fin...
cos(2x) = 2cos2(x) - 1 This is the identity. Therefore we can substitute in 2[cos2(x)] to be 2 multiplied by (1/4)2.Therefore cos(2x) = 2(1/4)(1/4) - 1 = 2/16 - 1 = 2/16 -...
2x^2 - 2x - 12
First of all, solving the equation 3n + 2 < 14 to find n. 3n < 14 -2 = 3n < 12. n < 12/3 = n < 4Secondly solve the equation 6n/(n^2+5) > 1 to find n. Collect all terms on one side of the...
(3x-4)/(x+2)(x-3) = A/(x+2) + B/(x-3)=> 3x-4 = A(x-3) + B(x+2)Let x = -2-10 = -5AA = 2Let x = 35 = 5BB = 1∴ (3x-4)/(x+2)(x-3) = 2/(x+2) + 1/(x-3)
←
383
384
385
386
387
→
Internet Safety
Payment Security
Cyber
Essentials